2019
DOI: 10.1002/ijc.32294
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting musculoskeletal burden and its development under letrozole treatment in early breast cancer patients

Abstract: One of the most common adverse events (AEs) occurring during treatment with aromatase inhibitors (AIs) is musculoskeletal pain. The aim of our study was to analyze the influence of preexisting muscle/limb pain and joint pain on the development of AI‐induced musculoskeletal AEs. Women eligible for upfront adjuvant endocrine therapy with letrozole were included in the PreFace study, a multicenter phase IV trial. During the first treatment year, they were asked to record musculoskeletal AEs monthly by answering q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
5
0
3
Order By: Relevance
“…Auch wenn der Nutzen einer adjuvanten endokrinen Therapie konsistent beschrieben ist, bricht ein relevanter Anteil von Patientinnen die Therapie frühzeitig ab. Neben Patientinnen-und Tumorcharakteristika ist hierbei das Auftreten von Nebenwirkungen einer der wichtigsten Prädiktoren für das frühzeitige Abbrechen einer Therapie [73,74,75].…”
Section: Nebenwirkungen Der Endokrinen Therapie Bei Prämenopausalen P...unclassified
“…Auch wenn der Nutzen einer adjuvanten endokrinen Therapie konsistent beschrieben ist, bricht ein relevanter Anteil von Patientinnen die Therapie frühzeitig ab. Neben Patientinnen-und Tumorcharakteristika ist hierbei das Auftreten von Nebenwirkungen einer der wichtigsten Prädiktoren für das frühzeitige Abbrechen einer Therapie [73,74,75].…”
Section: Nebenwirkungen Der Endokrinen Therapie Bei Prämenopausalen P...unclassified
“…With a large number of SERDs currently in clinical development 6 , 7 , the first phase III trial, the EMERALD trial, has now been published 8 . This study is of particular interest not only in terms of whether SERD treatment can overcome endocrine resistance based on an ESR1 mutation, but also in terms of a comparison between the oral SERD elacestrant and fulvestrant.…”
Section: Hr+ Her2−: the First Serd In A Phase III Trial And Biomarker...mentioning
confidence: 99%
“…Bei einer Vielzahl an SERDs, welche sich gerade in der klinischen Entwicklung befinden 6 , 7 , wurde nun mit der EMERALD-Studie die erste Phase-III-Studie veröffentlicht 8 . Nicht nur aufgrund der Frage, ob durch eine SERD-Therapie eine auf einer ESR1 -Mutation beruhende, endokrine Resistenz überwunden werden kann, sondern auch in Bezug auf einen Vergleich zwischen dem oralen SERD Elacestrant und Fulvestrant ist diese Studie von besonderem Interesse.…”
Section: Emerald-studie Veröffentlichtunclassified
“…A multicenter phase IV clinical trial showed that musculoskeletal pain during AI treatment occurred primarily in the first six months of treatment, with a higher incidence in patients without a pre-treatment history of musculoskeletal pain and greater post-treatment pain intensity in patients with a prior history of pain ( 16 ). Joint pain increased significantly during the first year of AI treatment and the health-related quality of life decreased.…”
Section: Poor Compliance Status and Risk Factors Such As Pain Sensati...mentioning
confidence: 99%